Measurement of jet pT correlations in Pb+Pb and pp collisions at √sNN = 2.76 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2017)
Measurements of dijet pT correlations in Pb+Pb and pp collisions at a nucleon–nucleon centre-of- mass energy of √sNN = 2.76 TeV are presented. The measurements are performed with the ATLAS detector at the Large Hadron Collider using Pb+Pb and pp data samples corresponding to integrated luminosities of 0.14 nb−1 and 4.0 pb−1, respectively. Jets are reconstructed using the anti-kt algorithm with radius parameter values R = 0.3 and R = 0.4. A background subtraction procedure is applied to correct the jets for the large underlying event present in Pb+Pb collisions. The leading and subleading jet transverse momenta are denoted pT1 and pT2 . An unfolding procedure is applied to the two-dimensional (pT1 , pT2 ) distributions to account for experimental effects in the measurement of both jets. Distributions of (1/N)dN/dxJ, where xJ = pT2 /pT1 , are presented as a function of pT1 and collision centrality. The distributions are found to be similar in peripheral Pb+Pb collisions and pp collisions, but highly modified in central Pb+Pb collisions. Similar features are present in both the R = 0.3 and R = 0.4 results, indicating that the effects of the underlying event are properly accounted for in the measurement. The results are qualitatively consistent with expectations from partonic energy loss models.